Carvedilol Ameliorates Early Diabetic Nephropathy in Streptozotocin-Induced Diabetic Rats - Morsy, Mohamed A. (Hindawi Publishing Corporation, 2014)
Diabetic nephropathy results in end-stage renal disease. On the other hand, carvedilol has been reported to have various pharmacological properties. The aim of this study therefore is to evaluate the possible protective effect of carvedilol on streptozotocin-induced early diabetic nephropathy and various mechanisms underlie this effect in rats. Single i.p. injection of streptozotocin (65 mg/kg) was administered to induce early diabetic nephropathy in Wistar rats. Oral administration of carvedilol at a dose level of 1 and 10 mg/kg daily for 4 weeks resulted in nephroprotective effect as evident by significant decrease in serum creatinine level, urinary albumin/creatinine ratio, and kidney index as well as renal levels of malondialdehyde, nitric oxide, tumor necrosis factor-α, and cyclooxygenase-2 with a concurrent increase in creatinine clearance and renal reduced glutathione level compared to diabetic untreated rats. The protective effect of carvedilol was confirmed by renal histopathological examination. The electron microscopic examination indicated that carvedilol could effectively ameliorate glomerular basement membrane thickening and podocyte injury. In conclusion, carvedilol protects rats against streptozotocin-induced early diabetic nephropathy possibly, in part, through its antioxidant as well as anti-inflammatory activities, and ameliorating podocyte injury.